2002
DOI: 10.1046/j.1440-0960.2002.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of depressive symptoms and quality of life in acne vulgaris patients treated with isotretinoin compared to antibiotic and topical therapy

Abstract: There have been recent concerns about the possible association between isotretinoin therapy and depressive symptoms. We conducted a prospective study to evaluate depressive symptoms and quality of life in acne patients having either isotretinoin or antibiotics/topical treatments. There were 215 patients (mean age 20 years) included in the study. Depression, quality of life and acne severity ratings were administered at baseline, 1 month, 3 months and end of treatment or 6 months, and compared between both trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 28 publications
7
63
1
7
Order By: Relevance
“…Other authors reported an onset of symptoms at two months after start of treatment (Bigby and Stern 1988;Burket and Storrs 1987;Hepburn 1990;Lindemayr 1986). Most of the other cases developed depression or committed suicide at some point during treatment (2-4 months after onset of treatment) although specific details are not always given (Barak et al 2005;Bravard et al 1993;Byrne and Hnatko 1995a;Cotterill and Cunliff 1997;Ng et al 2002;Scheinman et al 1990;Wysowski et al 2001b). Of course it is always possible (especially in the suicide cases) that symptoms were not reported at the time they actually started, or that patients denied depression.…”
Section: Temporal Association Between Isotretinoin Treatment and Deprmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors reported an onset of symptoms at two months after start of treatment (Bigby and Stern 1988;Burket and Storrs 1987;Hepburn 1990;Lindemayr 1986). Most of the other cases developed depression or committed suicide at some point during treatment (2-4 months after onset of treatment) although specific details are not always given (Barak et al 2005;Bravard et al 1993;Byrne and Hnatko 1995a;Cotterill and Cunliff 1997;Ng et al 2002;Scheinman et al 1990;Wysowski et al 2001b). Of course it is always possible (especially in the suicide cases) that symptoms were not reported at the time they actually started, or that patients denied depression.…”
Section: Temporal Association Between Isotretinoin Treatment and Deprmentioning
confidence: 99%
“…One of the patients was rechallenged with isotretinoin and experienced a recurrence of symptoms 3 months after re-initiation of treatment. Several other authors have reported individual cases of abatement of symptoms of depression and/or suicidality after discontinuation of isotretinoin (Bigby and Stern 1988;Bravard et al 1993;Burket and Storrs 1987;Byrne and Hnatko 1995b;Duke and Guenther 1993;Ng et al 2002). For instance, Barak reported that 4/5 patients who developed psychosis after receiving isotretinoin had an improvement in symptoms with cessation of isotretinoin and treatment with antipsychotics (Barak et al 2005).…”
Section: Cases Of Challenge/dechallenge Related To Isotretinoin and Dmentioning
confidence: 99%
“…On the other hand there is a significant relation between disease and quality of life, so that people who have more severe disease, had higher quality of life scores suggesting quality of life disorder. There is no significant relation between acne severity and quality of life in Matsoka's et al study, but there is a significant relation between lesions severity and patients quality of life in Hong's et al study, in Cobaler's et al study and in Yazirey's et al study (14)(15)(16)(17). Patients who have more severity had higher scores in quality of life they have reported more anxiety and depression.…”
Section: Discussionmentioning
confidence: 89%
“…Összességében a fennálló eredmények alapján csak kismértékben hozható összefüggésbe a depresszió az izotretinoin szedésével. A gyógyszer hatékonysága magasabb, mint 75%, ugyanakkor az alkalmazását mindenképpen mérlegelni szükséges, nemcsak depressziót okozó hatása miatt, hanem magas teratogenitása és egyéb mellékhatásai, például száraz bőr, fotoszenzitivitás, letargia, megváltozott májfunkcióértékek miatt is [60].…”
Section: Akne Kezelésére Alkalmazott Gyógyszerekunclassified